PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Herlambang, Setyarso; Darsono, Darsono (Diponegoro Journal of Accounting, 2015)
This research aims to analyze the effect of Good Corporate Governance (GCG) and firm size on earning management. GCG variable is proxied by board size, board compotition and audit comitee size. Firm size is measured by total assets. The dependent variable, earnings management, is measured by the discretionary accrual.Population of this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2012 and 2013. Purposive sampling method is using to take the samples so it takes 168 firm to use as data research. Method for testing the hypthesis in this research was conducted using multiple linear regression.The results show that board compotition and firm size have negative significant effect to earning management. This research also show that board size and audit commitee size have no effect related to earning management.